Expectations and reality: perceptions of support among African American breast cancer survivors. Issue 7 (3rd October 2019) - Felder, Tisha M.; Estrada, Robin Dawson; Quinn, Jada C.; Phelps, Kenneth W.; Parker, Pearman D.; Heiney, Sue P.
ABSTRACT: Objective: The experience of an illness such as breast cancer is not a static event. Just as physiological needs change as a patient transitions through diagnosis, treatment, to long-term survivorship, so too will their needs for social support. We applied a transitions theory framework to explore how African American women with breast cancer conceptualized and experienced support along their breast cancer journey. Design: We recruited 16 African American women with breast cancer from a regional cancer center in South Carolina to complete qualitative, semi-structured interviews. We iteratively examined verbatim transcripts using thematic analysis. Results: Three core themes emerged: 'I guess she was supposed to': When support meets patient expectations; 'I wasn't expecting that and that just made me feel so good': When reality exceeds expectations; and 'Don't try to make an invalid out of me': When support given wasn't what was desired. Survivors shared how their family, friends and clergy met their needs for emotional (e.g. prayer, sharing affirmations about God) and instrumental support (e.g. cooking meals, house cleaning). They emphasized how receiving emotional support from their healthcare providers was a pleasant surprise. However, survivors also described unexpected disappointments when family members offered support that was un-needed or un-desired. Conclusions : Applying transitions theory, we found that social support is a process of bidirectional negotiation where African American women with breast cancer perceive support as helpful and acceptable depending on who offers support, what type of support is offered, and when it is offered. Members of their social support network (e.g. family, friends, providers) should periodically assess the survivor's evolving needs to ensure the social support harmonizes with the needs and expectations of the survivor.